Alterations of Spinal Epidural Stimulation-Enabled Stepping by Descending Intentional Motor Commands and Proprioceptive Inputs in Humans With Spinal Cord Injury - Gill, Megan L.; Linde, Margaux B.; Hale, Rena F.; Lopez, Cesar; Fautsch, Kalli J.; Calvert, Jonathan S.; Veith, Daniel D.; Beck, Lisa A.; Garlanger, Kristin L.; Sayenko, Dimitry G.; Lavrov, Igor A.; Thoreson, Andrew R.; et al. (Frontiers in Systems Neuroscience, 2021)
Background: Regaining control of movement following a spinal cord injury (SCI) requires utilization and/or functional reorganization of residual descending, and likely ascending, supraspinal sensorimotor pathways, which may be facilitated via task-specific training through body weight supported treadmill (BWST) training. Recently, epidural electrical stimulation (ES) combined with task-specific training demonstrated independence of standing and stepping functions in individuals with clinically complete SCI. The restoration of these functions may be dependent upon variables such as manipulation of proprioceptive input, ES parameter adjustments, and participant intent during step training. However, the impact of each variable on the degree of independence achieved during BWST stepping remains unknown. Objective: To describe the effects of descending intentional commands and proprioceptive inputs, specifically body weight support (BWS), on lower extremity motor activity and vertical ground reaction forces (vGRF) during ES-enabled BWST stepping in humans with chronic sensorimotor complete SCI. Furthermore, we describe perceived changes in the level of assistance provided by clinicians when intent and BWS are modified. Methods: Two individuals with chronic, mid thoracic, clinically complete SCI, enrolled in an IRB and FDA (IDE G150167) approved clinical trial. A 16-contact electrode array was implanted in the epidural space between the T11-L1 vertebral regions. Lower extremity motor output and vertical ground reaction forces were obtained during clinician assisted ES-enabled treadmill stepping with BWS. Consecutive steps were achieved during various experimentally-controlled conditions, including intentional participation and varied BWS (60% and 20%) while ES parameters remain unchanged. Results: During ES-enabled BWST stepping, the knee extensors exhibited an increase in motor activation during trials in which either stepping was passive compared to active or during trials in which 60% BWS was provided compared to 20% BWS. As a result of this increased motor activation, perceived clinician assistance increased during the transition from stance to swing. Intentional participation and 20% BWS resulted in timely and purposeful activation of the lower extremity muscles, which improved independence and decreased clinician assistance. Conclusion: Maximizing participant intention and optimizing proprioceptive inputs through BWS during ES-enabled BWST stepping may facilitate greater independence during BWST stepping for individuals with clinically complete SCI.